(untitled) (2013)
In light of their excellent mechanical properties and other advantages over conventional systems for repairing and rehabilitating structures, fibre-reinforced polymers (FRPs) are commonly used to enhance the shear strength of RC members. Because of the relatively recent application of the technique in civil engineering, however, it is addressed in very few recommendations or guides. While the design guides in place contain a single, well defined and generally accepted procedure for calculating bending moments, they collectively propose a wide variety of numerical models for shear, none of which is universally acknowledged. The present article focuses on the calculation of ultimate shear strength and describes an experimental study in that context conducted on reinforced concrete beams retrofitted with unidirectional carbon fibre reinforced polymer (CFRP) fabric.